Analysis of linear eddy current brakes for maglev train using an equivalent circuit method - Jun Liu; Wei Li; Lijun Jin; Guobin Lin; Yan Sun; Zhiwei Zhang (IET Electrical Systems in Transportation)
Abstract An equivalent circuit method (ECM) is developed to analyse the linear eddy current braking system (ECBS) of the maglev train. The distribution of eddy current in the rail is represented by dividing the rail into a series of small segments in which the current is assumed to be uniform. Each segment is described as an equivalent circuit with parameters of resistance and inductance. The circuit parameters, such as self‐inductance and mutual inductance, are evaluated from the geometry parameters using an analytic method. The state equation derived from the circuit equations and the Newton's equations is solved using the Runge–Kutta method, from which the dynamic performance of the linear ECBS can be obtained. The accuracy and efficiency of the proposed ECM are verified by comparing the results with the one obtained from the finite element method. By adopting the developed ECM, the influence of parameters, such as speed, the exciting current and air gap of the linear ECBS, are analysed. The variation law of the linear ECBS with parameters is roughly grasped.